The Use of Equations to Organize Training for Both Shot Put and Discus Throws - Jassim Othman Al-Nuaimi, Muhammad; Jassim Muhammad Al-Kaldi, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The effectiveness of the shot put and discus throws depends to a large extent on resistance training with weights, which reach a single training unit, a group of tons, and those loads are distributed over a group of exercises such as squats, bench presses, front jerks, and snatches and cleans. The researchers determined which exercises are more specific to the effectiveness of discus and shot put throws, and after performing statistical operations according to predictive equations, the snatch exercise showed an effect on the effectiveness of the discus throw, and the front jerk exercise for the effectiveness of the shot put throws. After that, a proposed equation was applied that includes the results of the snatch exercise test to represent the strength and the mass of the disc to represent the resistance to predict the distance to achieve the effectiveness of throwing the disc according to the following: Disc throw distance = snatch test (kg) x 1 m / mass of disc (2 kg). A proposed equation was applied that includes the results of the front-jerk exercise test to represent strength and the iron ball mass to represent the resistance to predict the distance to achieve the effectiveness of shot put according to the following: The shot put distance = front-jerk test (kg) x 1 m / mass of the iron ball (shot put (7.260 kg)). Therefore, the throwing and pushing distance was derived from the two equations for each operation, and a correlation was made between it and the actual completion distance, which showed a very high correlation, suggesting the high accuracy of the proposed predictive equation when displaying the results.